2019
DOI: 10.1002/pssa.201800769
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rutile Titanium Oxide Thin Films as Battery Material Component Using Atomic Layer Deposition

Abstract: Herein, growth kinetics, crystal structure, and the uniformity of titanium oxide (TiO2) thin films prepared using atomic layer deposition (ALD) and plasma‐enhanced ALD (PE‐ALD) are studied. TiO2 thin films are grown using titanium tetrachloride (TiCl4), water, and oxygen precursors. Using ALD, TiO2 is grown in the temperature range of 270–310 °C thermally and in the range of 300–400 °C with PE‐ALD. In spite of the plasma process yielding better uniformity on planar structures, the optimized thermal process pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…In general, the interface properties strongly influence the nucleation behavior, such as heterogeneous and homogeneous nucleation, and crystallization kinetics in thin films. [38][39][40][41] The surfaces of the amorphous SiO 2 and polycrystalline TiN substrates have different characteristics such as surface energy, termination chemistry, roughness, and local structure. [36,38,41] However, the nucleation behavior of Li 4 Ti 5 O 12 thin films was not yet explained in literature.…”
Section: Crystallization Effect On the Electrochemical Behavior Of LI 4 Ti 5 O 12mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the interface properties strongly influence the nucleation behavior, such as heterogeneous and homogeneous nucleation, and crystallization kinetics in thin films. [38][39][40][41] The surfaces of the amorphous SiO 2 and polycrystalline TiN substrates have different characteristics such as surface energy, termination chemistry, roughness, and local structure. [36,38,41] However, the nucleation behavior of Li 4 Ti 5 O 12 thin films was not yet explained in literature.…”
Section: Crystallization Effect On the Electrochemical Behavior Of LI 4 Ti 5 O 12mentioning
confidence: 99%
“…[38][39][40][41] The surfaces of the amorphous SiO 2 and polycrystalline TiN substrates have different characteristics such as surface energy, termination chemistry, roughness, and local structure. [36,38,41] However, the nucleation behavior of Li 4 Ti 5 O 12 thin films was not yet explained in literature. Kia et al found that the crystalline phase of closely related TiO 2 ALD thin films is influenced by SiO 2 or TiN substrates upon annealing by favoring different nucleation mechanisms.…”
Section: Crystallization Effect On the Electrochemical Behavior Of LI 4 Ti 5 O 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have addressed the preparation of individual components of thin-film SSLIBs by ALD, such as cathodes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], anodes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and solid-state electrolytes [ 50 , 51 , 52 , 53 ]. Using several precursors in the ALD chamber allows the fabrication of all the SSLIB components using ALD equipment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among many functional nanomaterials, nanostructured TiO 2 are of great interest due to their unique properties and numerous practical applications [ 14 , 15 , 16 , 17 ]. The main interest in titania-based nanomaterials is basically associated with such high-efficient applications as lithium-ion batteries, solar cells, gas sensors, supercapacitors, etc., [ 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, active investigations are related to the photocatalytic activity of titania-based materials, including nanopowders and thin films [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%